Near-infrared luminescent erbium complexes with 8-hydroxyquinoline-terminated hyperbranched polyester. (24th March 2017) - Liu, Dan; Li, Chengjian; Xu, Yaling; Zhou, Dapeng; Wang, Hongmei; Sun, Ping; Jiang, Huasheng
Abstract: Novel 8-hydroxyquinoline-terminated hyperbranched polyesters (1-HBPQ and 2-HBPQ) were synthesized and characterized by 1 H-NMR and UV-Vis analyses. Then, two erbium complexes (1-HBPQ-Er 3+ -HQ and 2-HBPQ-Er 3+ -HQ) were prepared by using 1-HBPQ or 2-HBPQ as the macromolecular ligand and 8-hydroxyquinoline (HQ) as a second ligand. The FTIR spectra and UV-Vis absorption spectra confirmed that both the macromolecular ligand and the second ligand were successfully coordinated with Er 3+ ions. The erbium complexes emitted intense near-infrared luminescence at about 1530 nm, which corresponds to the 4 I 13/2 - 4 I 15/2 transition of Er 3+ ions. Moreover, their full width at half maximum (FWHM) values were greater than 80 nm. The erbium complexes exhibited good solubility in conventional solvents and excellent near-infrared luminescence properties, indicating their promising potential as gain medium materials in optical amplification devices. Graphical abstract: Highlights: Two novel 8-hydroxyquinoline-terminated hyperbranched polyesters were synthesized. Erbium complexes based on modified hyperbranched polyesters were prepared. Erbium complexes show intense near-infrared luminescence and wide FWHM.